(untitled) (Research, Society and Development, 2022)
The person with an ostomy undergoes several transformations, since he discovers the need to make a stoma. As a result, several feelings are experienced, leading to social isolation, negative financial commitment and psychological suffering. The work routine can be seen as the possibility of having their independence resumed, feeling useful and inserted in society, in addition to the possibility of bringing the financial support, necessary for their survival and that of their family. This study aims to understand, through the literature, the difficulties of the person with ostomy when returning to the job market; to characterize the feelings aroused during the rehabilitation process and to present the coping strategies of the ostomy patient and the contribution of nursing in this process. This is a descriptive, qualitative study of the reflective analysis type, prepared from a literature review, using the Virtual Health Library (VHL) database, in the following information base: International Health Science Literature (MEDLINE), Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO). It is concluded that the biopsychosocial changes caused by the presence of the stoma can make it difficult for the stoma patient to be included in the work, but the return to the work environment does not depend exclusively on himself, but on a social support network, promoting favorable conditions for the individual return to the labor market.